2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20192068
|View full text |Cite
|
Sign up to set email alerts
|

Current scenario in clinical trends of psoriasis in tertiary care hospital

Abstract: <p class="abstract"><strong>Background:</strong> Psoriasis is a common papulosquamous chronic, recurrent inflammatory skin disease with genetic predisposition and environmental factors acting as triggers. The current prevalence of common dermatoses will be useful for giving appropriate treatment for the patients. The aim of the study is to determine the different clinical pattern and prevalence of psoriasis in our institution.</p><p class="abstract"><strong>Methods:</stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The main aim of the treatment of psoriasis is to relieve the symptoms and prevent relapse. 36 Velappan R et al 37 concluded that usage of systemic steroids should be avoided as there is a severe flare, or even development of life-threatening generalised pustular psoriasis when steroids are tapered or stopped. In 2017, Thappa and Munisamy 5 reported that despite the prevalence of psoriasis in the Indian population and progress in research, India still lags in psoriasis research output.…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of the treatment of psoriasis is to relieve the symptoms and prevent relapse. 36 Velappan R et al 37 concluded that usage of systemic steroids should be avoided as there is a severe flare, or even development of life-threatening generalised pustular psoriasis when steroids are tapered or stopped. In 2017, Thappa and Munisamy 5 reported that despite the prevalence of psoriasis in the Indian population and progress in research, India still lags in psoriasis research output.…”
Section: Discussionmentioning
confidence: 99%
“…EC/CHAF Bangalore/2018/28 and an informed consent of the patients. The study size was calculated based on a previous study conducted by Velappan R et al 5 considering incidence of chronic plaque psoriasis "P" as 63.2%, with 95% confidence interval and permissible error (L) in the estimate of "p" as 10%, the sample size was calculated using the formula…”
Section: Methodsmentioning
confidence: 99%
“…EC/CHAF Bangalore/2018/28 and an informed consent of the patients. The study size was calculated based on a previous study conducted by Velappan R et al 5 considering incidence of chronic plaque psoriasis “P” as 63.2%, with 95% confidence interval and permissible error (L) in the estimate of “p” as 10%, the sample size was calculated using the formula ngoodbreak=[]()z20.25em()p0.25em()q/()d2 where, n is the sample size, z is the value for the selected alpha level, that is, 1.96 for 95% confidence interval, p is the estimated prevalence of attribute that is present in the population, q is 1‐p, d is the acceptable margin of error of 10% for proportion being estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriatic lesions are well-defined erythematous indurated plaques with silvery white scales. Autoimmune diseases like vitiligo, lichen planus, bullous pemphigoid and alopecia areata are also known to be associated in psoriatic patients (Velappan et al 2019).…”
Section: Introductionmentioning
confidence: 99%